Assessing microbiome engraftment extent following fecal microbiota transplant with q2-fmt. - Chloe Herman; Evan Bolyen; Anthony Simard; Liz Gehret; J Gregory Caporaso (PLoS Computational Biology)
We present q2-fmt, a QIIME 2 plugin that provides diverse methods for assessing the extent of microbiome engraftment following fecal microbiota transplant. The methods implemented here were informed by a recent literature review on approaches for assessing FMT engraftment, and cover aspects of engraftment including Community Coalescence, Indicator Features, and Resilience. q2-fmt is free for all use, and detailed documentation illustrating worked examples on a real-world data set are provided in the project's documentation.